Global research productivity in the field of discectomy on lumbar disc herniation: A systematic bibliometric analysis - Li, Wei-Shang; Yan, Qi; Li, Gao-Yu; Chen, Wen-Ting; Cong, Lin (Frontiers in Surgery, 2023)
Objective To evaluate the global research productivity in the field of discectomy for lumbar disc herniation (LDH) through bibliometric analysis and mapping knowledge domains. Methods A systematic literature search was performed on the Web of Science (WoS), including the Science Citation Index Expanded (SCIE) database and PubMed. The number of publications, countries of publications, journals of publications, total citation frequency, impact factors of journals, and Institutional sources were analyzed by Microsoft Excel 2019, the Online Analysis Platform of Bibliometrics, and VOSviewer. Hotspots were also analyzed and visualized based on VOSviewer. Results A total of 2,066 papers were identified. The United States ranked first in the number of total citations (7,970). China ranked first in the number of publications (556, 26.9%), which has surpassed the United States in terms of the number of publications published annually since 2016. Wooridul Spine Hospital published the most papers (43). For journals, Spine has published the largest number of papers (289) in this field with the most citation frequencies (6,607). Hotspots could be divided into three clusters: surgery, lumbar disc herniation, and diagnoses. The most recent topic that appeared was symptomatic re-herniation. Conclusions The United States is the most significant contributor to the development of discectomy for LDH. The current research focus of discectomy on LDH was the comparison between surgical approaches and evaluation of current minimally invasive discectomy. At present, minimally invasive techniques, such as endoscopic discectomy, cannot completely replace non-endoscopic discectomy (open discectomy and microdiscectomy) through bibliometric analysis and mapping knowledge domains.